Maternal Plasma Phosphatidylcholine Fatty Acids and Atopy and Wheeze in the Offspring at Age of 6 Years. (25th September 2012) - Pike, Katharine C.; Calder, Philip C.; Inskip, Hazel M.; Robinson, Sian M.; Roberts, Graham C.; Cooper, Cyrus; Godfrey, Keith M.; Lucas, Jane S. A.
Abstract : Variation in exposure to polyunsaturated fatty acids (PUFAs) might influence the development of atopy, asthma, and wheeze. This study aimed to determine whether differences in PUFA concentrations in maternal plasma phosphatidylcholine are associated with the risk of childhood wheeze or atopy. For 865 term-born children, we measured phosphatidylcholine fatty acid composition in maternal plasma collected at 34 weeks' gestation. Wheezing was classified using questionnaires at 6, 12, 24, and 36 months and 6 years. At age of 6 years, the children underwent skin prick testing, fractional exhaled nitric oxide (FENO) measurement, and spirometry. Maternal n -6 fatty acids and the ratio of n -3 to n -6 fatty acids were not associated with childhood wheeze. However, higher maternal eicosapentaenoic acid, docosahexaenoic acid, and total n -3 fatty acids were associated with reduced risk of non-atopic persistent/late wheeze (RR 0.57, 0.67 and 0.69, resp. P = 0.01, 0.015, and 0.021, resp.). Maternal arachidonic acid was positively associated with FENO (P = 0.024 ). A higher ratio of linoleic acid to its unsaturated metabolic products was associated with reduced risk of skin sensitisation (RR 0.82, P = 0.013 ). These associations provide some support for the hypothesis that variation in exposure to n -6 and n -3 fatty acids during pregnancy influences the risk of childhood wheeze and atopy.